Comparative study on antibacterial mechanism of shikimic acid and quinic acid against Staphylococcus aureus through transcriptomic and metabolomic approaches. (January 2022) - Bai, Jinrong; Wu, Yanping; Bu, Qian; Zhong, Kai; Gao, Hong
Abstract: Shikimic acid (SA) and quinic acid (QA), widely found in many natural plants, have been reported to exhibit prominent antibacterial activity in our previous studies. In this study, their inhibitory mechanism against Staphylococcus aureus was comparatively investigated for the first time by combined transcriptomic and metabolomic analyses. Bioinformatic analysis results revealed SA and QA had remarkably different action mechanism against S. aureus at multi-targets and multi-pathways. These two organic acids disturbed oxidative phosphorylation pathway, and changed glycerophospholipids and fatty acids levels to interfere with the membrane fluidity. Besides, only SA affected the normal functions of potassium channel and calcium channel. After penetrated cell membrane, SA and QA influenced the ribosome functions and aminoacyl-tRNA synthesis, thus disordering the protein synthesis. Furthermore, SA interfered with the pyruvate metabolic pathways, while QA damaged the synthesis of l -lysine and peptidoglycan to inhibit cell wall synthesis and cell division. This study lays theoretical foundations for the application of SA and QA as novel natural antibacterial agents in foods. Highlights: This is the first joint omics research elucidating the antibacterial mechanism of SA and QA. The action mechanism of SA and QA against S. aureus had an apparent difference. SA and QA both influenced oxidative phosphorylation, membrane fluidity and protein synthesis. SA affected normal ion channels and pyruvate metabolic pathways. QA damaged l -lysine and peptidoglycan synthesis to inhibit cell wall synthesis and cell division.